Volume, increment and growth in clonal and seminal canopy damages stands of Teak - Gava, Fernando Henrique (2021)
The aim of the study was to adjust  volume and growth models and analyze the increments of six years old teak clones and seminal material  influenced by canopy breakage.  Diameter at breast height (DBH), commercial (hc) and total height (h) were measured in a randomized block experiment in with five treatments using clonal and seminal teak material. Ten trees from each treatment were cubed and the mean volumes were compared models (DBH, h and volume). Schumacher-Hall model was chosen for clone 68 and the Modified Prodan model for the other treatments. DBH and volume were expressed by the Moissev model and height by the Backman model. DBH and h CAI and MAI are negatively affected by canopy damage and clones had the greatest gains in productivity, especially the clone 61.